2021
DOI: 10.1371/journal.pntd.0008885
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological surveillance of hand foot and mouth disease in paediatric patients and in community: A Singapore retrospective cohort study, 2013–2018

Abstract: Background While hand, foot and mouth disease (HFMD) is primarily self-resolving—soaring incidence rate of symptomatic HFMD effectuates economic burden in the Asia-Pacific region. Singapore has seen a conspicuous rise in the number of HFMD cases from 2010s. Here, we aims to identify the serology and genotypes responsible for such outbreaks in hospitals and childcare facilities. Methods We studied symptomatic paediatric HFMD cases from 2013 to 2018 in Singapore. Surveillance for subclinical enterovirus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…320/322 CVA16 patients with available demographic and clinical information were included for analysis in the present study. Most (59.4%) of these patients were male, in agreement with previous reports ( Le et al, 2020 ; Min et al, 2021 ). The median age was 20.82 months.…”
Section: Resultssupporting
confidence: 93%
“…320/322 CVA16 patients with available demographic and clinical information were included for analysis in the present study. Most (59.4%) of these patients were male, in agreement with previous reports ( Le et al, 2020 ; Min et al, 2021 ). The median age was 20.82 months.…”
Section: Resultssupporting
confidence: 93%
“…These four genotypes were also with the highest frequency in France during 2014-2015 ( 15 ). CV-A6 was detected a high proportion in HFMD or herpangina children in vast locations and time span ( 16 ), and it was the predominant pathogen in Guangdong in 2015, Singapore in 2013-2018 and Guizhou in 2019 ( 17 , 18 ). Studies ( 19 ) showed that CV-A6 detection rate was low in 2010-2012, then increased in 2013, 2015, 2017 and remained high in 2018, while decreased in 2014, 2016 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…CVA16 and EVA71 are the two best known viruses which cause mild herpangina and hand-foot-and-mouth disease (HFMD) in young children. Several HFMD outbreaks associated with co-circulation of EVA71 and CVA16 have been reported in China, Japan, Korea, Malaysia, Singapore, Vietnam, and Thailand [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Of notice, there are three fatal reports of CVA16 infection: one is of a child who had HFMD associated with myocarditis, the second is of an adult who had pneumonitis, and the third is of a child who had HFMD associated with acute pancreatitis [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%